Audit Partner Characteristics and Their Impacts on Audit Quality: Evidence from around the World - Lingting Jiang; Janean Rundo; Linna Shi; Nan Zhou (Encyclopedia)
Public company audits are not homogenous. Varying audit partner attributes, including gender, age, location, and expertise, play important roles in explaining audit outcome disparities. The extant literature underscores the influence of firm-level and office-level differences, in areas such as size, culture, and industry expertise, in shaping audit outcomes. Commonwealth countries, such as the U.K., Australia, New Zealand, and Continental European countries, along with Asian economic entities, mandate the disclosure of audit partner names. Consequently, significant research efforts have been devoted to investigating the impact of audit partner characteristics on audit outcomes in these jurisdictions. With the adoption of Public Company Accounting Oversight Board (PCAOB) Rule 3211, mandating disclosure of audit engagement partner details for U.S.-registered public accounting firms on Form AP, there has been a surge in U.S. firm research exploring the significance of audit partner characteristics on audit outcomes in recent years. This paper outlines research that considers audit partner attributes’ influence on audit partner selection and audit quality across different economic entities. This entry contributes by synthesizing findings from recent research across diverse economic contexts, including the recently available insights from U.S.-based audits. The analysis of this entry not only provides insights into the current state of audit partner research but also delineates avenues for future research on this topic.